Comparison of laryngeal mask airway supreme™ versus endotracheal intubation in positive pressure ventilation with muscle relaxant for intraoperative and postoperative conditions - Singam, Amol Prakash; Jaiswal, Arpita Ashok; Chaudhari, Ashok Ramkrishna (International Journal of Research in Medical Sciences, 2017)
Background: Laryngeal Mask Airways are increasingly being used now a day as an option to endotracheal intubation, as it is less invasive and causes less discomfort in the postoperative period. The aim of this study was to evaluate the clinical use of the laryngeal mask airway SupremeTM in patients undergoing elective gynaecological surgeries under general anaesthesia and compare it with endotracheal intubation. Methods: 60 ASA I and II females, having BMI <30kg.m-2 in the range of 20-50 years of age, scheduled for elective gynaecological surgeries were randomly allocated to one of the two groups according to the device used (LMAS or ETT). Time required for insertion, number of attempts, hemodynamic response to insertion/removal and incidence of immediate and late postoperative complications such as coughing, laryngospasm, sore throat, dysphagia etc. were assessed. Results: Number of attempts for successful insertion was similar but time required for LMA Supreme™ insertion was significantly less (25.40±12.90 versus 33.27±14.82 sec) similarly, time required for nasogastric tube insertion was significantly more in ETT group (30.28±16.22 versus 21.93±12.64 sec). No episode of failed ventilation or hypoxia was recorded. The changes in hemodynamic parameters were significantly higher after endotracheal intubation and during extubation. Incidence of postoperative complications was significantly higher after endotracheal intubation (p<0.05). Conclusions: The LMA Supreme™ is a suitable alternative to endotracheal intubation during general anaesthesia for elective gynaecological surgeries with the added advantage of less hemodynamic response during airway management and lower incidence of postoperative complications.